Elastic resonant and nonresonant differential scattering of quasifree electrons from B4+(1s) and B3+(1s2) ions - Benis, E. P.; Zouros, T. J. M.; Gorczyca, T. W.; González, A. D.; Richard, P. (My University, 2004)
High-resolution doubly differential cross-section measurements and calculations for quasifree electrons elastically scattered through 180° from ground-state He- and H-like boron ions are presented. The measurements, covering the entire 1s2lnl′(for B3+) and 2lnl′(for B4+) Rydberg series populated by resonant excitation, were performed by zero-degree Auger projectile electron spectroscopy of 3.91MeVB4+ and 3.08–7.48MeVB3+ ions in collisions with H2 targets. The projectile energy dependence study is used to further investigate other background contributions such as direct electron capture, direct excitation, and nonresonant transfer excitation. R-matrix calculations, particularly sensitive at this large scattering angle to electron correlation, exchange, and interference effects, are found to be in excellent overall agreement within the electron scattering model.